Eksplorasi Peran Kepemimpinan dalam Membangun Motivasi Anggota dan Kinerja Organisasi: Stusi Kasus pada Himpunan Mahasiswa Sipil Kabupaten Lamongan - Zildjian Aura Dewa Saldana; Dadang Wiratama; Ali Musta’in (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to explore in depth the role of leadership in building member motivation and improving organizational performance at the Civil Engineering Student Association in Lamongan Regency. The method used is qualitative research with a case study approach, which allows researchers to understand the phenomenon contextually and comprehensively. Data were collected through observation techniques, in-depth interviews, and documentation of the organization's administrators and members who were actively involved in various activities. The results of the study indicate that participatory and communicative leadership styles have a significant role in increasing member motivation. This is realized through giving appreciation, involving members in the decision-making process, and implementing open and transparent communication. High member motivation has a positive impact on improving organizational performance, particularly in the successful implementation of planned work programs. However, this study also found several obstacles, such as miscommunication, time constraints, and differences of opinion among members that can affect organizational effectiveness. Therefore, an adaptive and solution-oriented leadership strategy is needed. Overall, this study confirms that leadership, motivation, and organizational performance are closely related and significantly influence each other.